PENGEMBANGAN KURIKULUM PAI BERBASIS KOMPETENSI ABAD 21 - Zainuri, Habib (PASCASARJANA UNISNU, 2024)
This study aims to respond to the dynamic and fast-paced educational needs of the digital era in the 21st century by developing a curriculum for Islamic Religious Education (IRE) that integrates essential competencies such as critical thinking, creativity, collaboration, and communication. The methodology employed is an in-depth literature review, combining various prior research sources to formulate a holistic approach to curriculum development that is both applicable and relevant. Key findings from this study indicate that integrating technology into IRE significantly enhances student interest and motivation, while also facilitating the development of critical 21st-century skills. Additionally, the study reveals that innovative curriculum implementation requires effective collaboration between educators, educational institutions, and policymakers. This research also emphasizes the importance of adapting the curriculum to local values and the Indonesian culture to ensure relevance and acceptance in a broader social context. Recommendations include the need for intensive training for educators, robust infrastructure support, and an ongoing process of evaluation and revision of the curriculum to maintain its relevance and effectiveness.